The impact of financial crisis on the short-term interaction betwee Balkan stock markets - Julijana Angelovska (UTMS Journal of Economics, 2017)
The aim of this study is to examine the impact of financial crises on the short-term interaction between stock market returns of the Macedonian, Serbian and Croatian equity markets. Daily data sample spans from January 4th 2006 to March 31st 2017and based on detected Zivot-Andrews structural break point tests three subsamples are created: Subsample 1- January 4th 2006 to December 31th 2007, the period characterized as period of growth on the three Balkan stock markets, Subsample 2 - January 1st2008 to June 30th 2011, turbulent period for the stock markets and Subsample3 - July 1st2011 to March 31st 2017, after crisis period. Using simple Correlation and Granger-causality tests it is found that three stock markets interacted mostly in the crisis period. A bi-directional pattern of causality is detected for all pairs, except for the relation Macedonia-Serbia. Via variance decomposition and impulse response functions the extent of the interaction within Subsample 2 is analyzed and as a most influential stock market that transmits the changes on the others is the Croatian stock market. From a perspective of Macedonian and Serbian investors, this means that they can benefit following the movement of the Croatian stock market.
Keywords: G15; F36; C32; 330; Dynamic Relationship; Granger Causality; Croatia; Serbia; Macedonia